Comparative Study Based on the Utilization of Polystyrene Foam and High-Density Polyethylene in Lightweight Concrete - Alaud, Salhin (Sharwes Scientific Journal, 2025)
The present study aims to find the influence of the Polystyrene Foam (PSF) and the High-Density Polyethylene (HDPE) on obtaining lightweight concrete. Three types of mixtures containing cement and sand were prepared. The sand was partially replaced by PSF in one mixture, while it was replaced by HDPE in the other, in proportions (5%, 7%, 10%, 15%) for both. Certain characteristics such as density, and compressive strength, were analysed from experiment results. In addition, the influence of PSF and HDPE as replacements of fine aggregate was analysed and compared with the reference mix of concrete. The results highlighted the concrete density decreased significantly with the increase of PSF replacement and moderately when the HDPT replacement ratio in the mixture increased. In the same way, the compressive strength decreased significantly when adding PSF and moderately when adding HDPE compared to the control reference mixture. A comparison was made between the two types of mixtures and the results showed that HDPE concrete is much higher than PSF concrete in terms of density and compressive strength.